2015
DOI: 10.1111/ijs.12459
|View full text |Cite
|
Sign up to set email alerts
|

Solitaire™ with the Intention for Thrombectomy as Primary Endovascular Treatment for Acute Ischemic Stroke (SWIFT PRIME) Trial: Protocol for a Randomized, Controlled, Multicenter Study Comparing the Solitaire Revascularization Device with IV tPA with IV tPA Alone in Acute Ischemic Stroke

Abstract: RationaleEarly reperfusion in patients experiencing acute ischemic stroke is critical, especially for patients with large vessel occlusion who have poor prognosis without revascularization. Solitaire™ stent retriever devices have been shown to immediately restore vascular perfusion safely, rapidly, and effectively in acute ischemic stroke patients with large vessel occlusions.AimThe aim of the study was to demonstrate that, among patients with large vessel, anterior circulation occlusion who have received intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
157
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(172 citation statements)
references
References 20 publications
3
157
0
4
Order By: Relevance
“…The design of these studies has been reported previously. 3,[7][8][9] Briefly, the SWIFT trial was a randomized clinical trial that ran from 2010 to 2011, in which patients with acute ischemic stroke and an angiographically confirmed occlusion of a the proximal cerebral artery were allocated to treatment with a stent retriever (Solitaire; Covidien, Irvine, California) or the Merci device (Concentric Medical, Mountain View, California). SWIFT had a roll-in phase during which all patients were treated with a stent retriever, and these patients were included in the current study.…”
Section: Description Of Studies and Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of these studies has been reported previously. 3,[7][8][9] Briefly, the SWIFT trial was a randomized clinical trial that ran from 2010 to 2011, in which patients with acute ischemic stroke and an angiographically confirmed occlusion of a the proximal cerebral artery were allocated to treatment with a stent retriever (Solitaire; Covidien, Irvine, California) or the Merci device (Concentric Medical, Mountain View, California). SWIFT had a roll-in phase during which all patients were treated with a stent retriever, and these patients were included in the current study.…”
Section: Description Of Studies and Patient Selectionmentioning
confidence: 99%
“…[7][8][9] The aim was to achieve successful recanalization of the territory of the occluded vessel. The use of a balloon-guide catheter was mandatory in STAR and SWIFT and optional in SWIFT PRIME.…”
Section: Mt Proceduresmentioning
confidence: 99%
“…Over the past decade endovascular management of AIS has rapidly improved and several catheter-based treatment systems have been developed. To date, 5 randomized controlled trials have shown that endovascular clot retrieval in addition to best medical treatment with or without intravenous recombinant tissue plasminogen activator (rtPA) improves outcome in patients with stroke occurring in the anterior circulation with proximal vessel occlusion [5][6][7][8][9]; however, despite minimally invasive device systems, endovascular procedures still carry a risk of iatrogenic complications, poten-tially worsening the outcome. Manipulation of the catheter, guidewire or thrombectomy devices could cause vessel wall injury.…”
Section: Introductionmentioning
confidence: 99%
“…7,[9][10][11][12][13] Recent clinical studies demonstrating the value of mechanical thrombectomy for acute ischemic stroke (AIS) did not include a significant number of elderly patients. [14][15][16][17] We performed a post hoc analysis of 2 prospective core lab-reviewed studies assessing mechanical thrombectomy by using new-generation devices (stent retrievers) for AIS to determine whether the benefit of reperfusion was constant across age groups, including the older population.…”
mentioning
confidence: 99%